Amity Elderly Home with Architectural Behaviour - Napitupulu, Putri Yemima Fressy; Bahri, Samsul (Komunitas Menulis dan Meneliti (Kolibi), 2024)
Loneliness among older adults is a significant public health concern due to its adverse effects on mental and physical health. It is characterized by a severance of relationships, particularly from social networks, family, and community. Despite being a taboo subject, loneliness is associated with various negative outcomes, including cardiovascular diseases, depression, anxiety, cognitive decline, dementia, and stroke [1,3]. Studies have shown that loneliness is linked to depression, with a meta-analysis indicating that loneliness increases the incidence of depression by 1.65 times in the elderly compared to those who are not lonely[4]. Additionally, loneliness is related to chronic illnesses and poor health perceptions, with social and emotional loneliness significantly associated with depression and chronic illnesses, respectively[2]. The prevalence of loneliness varies across populations, age, and definitions used, but its impact on health and well-being is undeniable. Therefore, addressing loneliness among older adults is crucial for improving their overall health and well-being, as well as reducing the strain on social care resources and clinical practice[2,5]. Elderly homes are designed specifically for the elderly, yet loneliness remains a significant issue within them. Loneliness in the elderly can be caused by various factors, such as being away from family, decreased social interaction, and lack of spiritual fulfillment. Therefore, effective elderly home design must consider the psychological needs of the elderly and provide adequate facilities to enhance their quality of life. Behavioral architecture plays a crucial role in creating a comfortable and safe environment for the elderly. Required facilities include spaces that facilitate social interaction, physical activities, and spiritual practices. Additionally, elderly homes must have a safe and effective care system in place to identify and manage patient risks. Thus, designing an elderly home that is specifically designed to mitigate loneliness in the elderly must consider their psychological and physical needs and provide adequate facilities to enhance their quality of life. This way, the elderly can feel more comfortable and cared for, and have opportunities to address the feelings of loneliness they experience.